THE COMPLEX IMPLICATIONS OF FINTECH FOR FINANCIAL INCLUSION. - HUGHES, HEATHER (Law & Contemporary Problems, 2021)
The article discusses the issues over the use of financial technology (fintech) to promote financial inclusion and sustainability. Other topics include the systemic risks posed by fintech, some emerging fintechs like online mobile banking, cryptocurrencies, and blockchain-based transaction platforms, as well as how said platforms comport with property, contract and entity laws.